MASALAH PEMENUHAN KEBUTUHAN AIR BERSIH TIGA DESA DI KABUPATEN ENDE - Rahardjo, Petrus Nugro (Center for Environmental Technology, 2008)
Clean water supply is still a very difficult problem for small villages, especially in County Ende, NTT. Three villages, ie Detukeli, Ndetundora I and Ndetundora II, are the examples. The real problem is the settlement living in the area which do not have enough potential of water resources.There are some potential surface water resources, but they are located more than 3 km from the village settlement. One of the potential rivers is so separated by a big hill, that the people have to walk for a long distance to reach the clean water resource. To solve the problem, it is very important to develop a transmition piping, including the distribution net and a hidram water pumping system. To construct a complete water supply system needs a lot of investation. For only Village Detukeli as an example, it needs approximately almost 2 thousand million rupiahs. Ã‚Â Kata Kunci : Clean water supply, limited potential of water resources